Synbiotic microcapsules of Bacillus subtilis and oat β-glucan in Nile tilapia diets - Alves, Angelica Priscila do Carmo (2022)
Probiotics are defined as microbial food additives which beneficially affect the host by improving its intestinal microbial balance. However, the viability of microorganisms with probiotic action may be impaired during passage through the hosts gastrointestinal tract or by the conditions of food storage. Therefore, microencapsulation appears as a promising technique in the protection of probiotics, eliciting a favorable microenvironment for the encapsulated microorganism. However, there is still no complete map on the effects of microencapsulation to extend the viability of probiotics. Considering these factors, this project aims at investigating the effects of a synbiotic combination of β-glucan and Bacillus subtilis, free and microencapsulated by the spray-drying technique, in diets for Nile tilapia, Oreochromis niloticus. The first chapter of this thesis explains the theoretical framework that allow the critical evaluation of the subsequent chapters. The second chapter, therefore, consists of the development and characterization of Bacillus subtilis and β-glucan microcapsules using sodium alginate as a complementary biopolymer to evaluate the survival of the probiotic to the microencapsulation process and resistance to simulated tilapia gastrointestinal fluids. The third chapter is the application of the microcapsules in a growth trial in a completely randomized design with five treatments and five replicates: C Control, no synbiotic added; 0.1%S - 0.1% of non-encapsulated synbiotic; 0.2%S - 0.2% of non- encapsulated synbiotic; 0.1%SM - 0.1% microencapsulated synbiotic; 0.2%SM - 0.2% microencapsulated synbiotic. At the end of the growth trial, hematological, histological and sequencing analysis were performed to characterize the effects of the addition of microencapsulated synbiotics to the diets in the improvement of the integrity of the intestinal epithelium and performance of the animals. At the end of the growth trial, fish were submitted to immunological challenge by the bacterium Aeromonas hydrophila to evaluate the survival rate and analysis of the innate immune system to detect the action of the synbiotic in the free or microencapsulated form. Overall, probiotics encapsulated by the spray-drying technique showed greater viability when compared to free probiotics during storage and in vitro studies. Also, the encapsulated probiotics were more effective when added to tilapia diets, which resulted in better animal performance.